Analysis of Village Fund Allocation Management in Improving Community Welfare in Watutau Village, Lore Peore Sub-district, Poso District - Rengku, Stovan; Yunus, Rita; Tope, Patta; Jaya, Andi Herman; Yunus, Santi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The government aims to assist villages in achieving independence and self-sufficiency through the allocation of Village Fund. This fund is divided into 30% for the operational expenses of the Village Government and BPD (Village Consultative Body), and 70% for enhancing community empowerment and building the capacity of the Village Government. The objective of this study is to examine how ADD is managed in empowering the community of Watutau village. The research methodology employed is descriptive qualitative research conducted in Watutau Village, Lore Peore Sub-district. Data collection involved triangulation methods including in-depth interviews with village officials and community members, direct field observations, and comprehensive document analysis of village financial records. The findings of the research indicate that some of the Village Fund allocated for community empowerment is utilised for covering the operational costs of the village government and BPD. This allocation disparity (93.42% for governance versus 6.58% for empowerment) contradicts the mandated 30/70 distribution ratio and undermines the fund's primary purpose of fostering community self-sufficiency and development. These results highlight the need for enhanced oversight mechanisms and policy reforms to ensure Village Fund allocation achieves its intended community empowerment objectives.